Analisis Exergoeconomic Gas Engine Siklus Miller Dengan Bahan Bakar Biogas Berbahan Baku POME - Ahmad Hasnul Fajri Arsyah; Romy Romy; Iwan Kurniawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Many alternatives have been made to Minimalized energy usage. One of them performs exergy analysis and exergoeconomic analysis. This concept of analysis, not only taking into account the quantity of energy but also the quality of the energy (the second law of thermodynamics). Exergoeconomic analysis, is an analysis that combines the exergy analysis with an economic approach (cost). Exergoeconomic analysis was done by taking data at PLTBg Tandun. The analysis was initiated by conducting economic analysis. Analyses conducted to figure out the total value of the waste from the Diesel PLTBg per year and the price of electricity/kWh. There ware 3 aspects of costs that we calculated cost of investment, operational maintenance fix costs, (employee salaries and benefits), and the operational maintenace. Of the each variable cost value were, the investment costs 0.016/kWh, for to investment cost 0.030/kWh, OM Fix the cost 0.009/kWh variable OM. The value of total cost loss for gas engine due to the destruction of the first period exergy is 7.116/hour, They are cost of losses for each component is the fuel space worth 7.09/hour, for combustion chamber, 0.043/hour, for compressor, 0.033/hour for turbocharge. While total cost loss value due to destruction of exergy the second period is 5.626/hour. They were of losses for each component is the fuel space worth 5.22/hour, compressor 0.393/hour, turbocharge 0.013/hour. Keywords: exergy, exergoeconomic, gas engine, biogas